Reforms of the Jadids regarding the development of pedagogical ideas. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The funds of the Central Archive of the Republic of Uzbekistan contain many materials related to the history of Central Asian modernism. Of particular interest are the materials of the Foundation "Office of the Governor General of Turkestan" (F.I-1), which contains important documents related to the political activities of the Jadids until 1917. the social foundations of the Jadid movement, the activities of the Jadid leaders, the attitude of the country's royal administration to them.